2016
DOI: 10.1016/j.irfa.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The earnout structure matters: Takeover premia and acquirer gains in earnout financed M&As

Abstract: In this article, based on both parametric and non-parametric methods, we provide a robust solution to the long-standing issue on how earnouts in corporate takeovers are structured and how their structure influences the takeover premia and the abnormal returns earned by acquirers. First, we quantify the effect of the terms of earnout contract (relative size and length) on the takeover premia. Second, we demonstrate how adverse selection considerations lead the merging firms to set the initial payment in an earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
3
23
0
1
Order By: Relevance
“…The findings suggest that, for two comparable deals, a missing covariate should increase the likelihood of the acquirer to low investor scrutiny by more than 50% to invalidate our PSM-based conclusions. When assessed relative to previous findings in the corporate finance literature (Barbopoulos and Adra, 2016;Peel and Makepeace, 2012), this evidence suggests that our findings are, to a large extent, insensitive to the effect of a confounding variable.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The findings suggest that, for two comparable deals, a missing covariate should increase the likelihood of the acquirer to low investor scrutiny by more than 50% to invalidate our PSM-based conclusions. When assessed relative to previous findings in the corporate finance literature (Barbopoulos and Adra, 2016;Peel and Makepeace, 2012), this evidence suggests that our findings are, to a large extent, insensitive to the effect of a confounding variable.…”
Section: Introductionsupporting
confidence: 59%
“…For instance, Peel and Makepeace (2012) report a level of 1.55 to highlight the robustness of their conclusion regarding the premium received by accounting auditors. Likewise, Barbopoulos and Adra (2016) report a level of 1.50 to highlight the robustness of their conclusion with respect to the initial payments in earnout financed deals.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Within the first research stream, another strand of studies focuses on the consequences of earnouts in terms of market reactions to M&A deal announcements, providing mixed results. While Kohers and Ang () and Barbopoulos and Sudarsanam () find that acquisitions that involve earnouts are associated with higher announcement period returns, McNichols and Stubben () and Barbopoulos and Adra () do not find a significant relationship between the use of earnouts and bidders’ returns upon announcement. More recently, Barbopoulos, Paudyal, and Sudarsanam () show, for a sample of deals announced by US firms between 1986 and 2013, that the relationship between announcement returns and the use of earnouts is significantly negative.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Understanding this will make it possible in the future for researchers or business practitioners to correctly apply the patterns obtained in other countries or other industries. The research work cited at [7] addresses the issue of the dependence of the premium in the deal and the length of the deal's processing period. The authors concluded that increasing the time interval between the moment of hearing of the deal and the moment of announcement of the deal means an increase in premium.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The authors concluded that increasing the time interval between the moment of hearing of the deal and the moment of announcement of the deal means an increase in premium. At the same time, the research methodology in [7] uses the CAR principle, so we would like to check these findings with respect to the relative premium. Industry characteristics of mergers and acquisitions of Russian companies are analysed in the research work cited at [3].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%